Representasi Kekerasan dan Kenakalan Remaja pada Serial Anime Tokyo Revengers - Adevy Vanie; Zahra Javiera (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to understand the Representation of violence and juvenile delinquency in the anime series Tokyo Revengers. This study uses a qualitative approach with semiotic analysis of Charles Sanders Peirce in the form of sign, object, and interpretant. Where researchers conducted an analysis by selecting each scene that contains scenes of violence and juvenile delinquency, then photographing each scene of violence and juvenile delinquency contained in the Tokyo Revengers anime series. selecting each scene that contained scenes of violence and juvenile delinquency. The results of this study show that in the anime series Tokyo Revengers there is violence both physical violence and verbal violence. Physical violence in the form of hitting, kicking, slapping, stomping, hitting using blunt weapons. As well as verbal violence in the form of rude speech, threats, shouts, swearing with harsh words, and also fighting sheep. There are also forms of juvenile delinquency such as fighting, smoking, underage motorcycle riding without equipment, bullying, stealing, and prostitution. Where violence and juvenile delinquency that occurs is a form of symbolic interactionism.